Catalytic effect of EG and MoS2 on hydrolysis hydrogen generation behavior of high‐energy ball‐milled Mg‐10wt.%Ni alloys in NaCl solution—A powerful strategy for superior hydrogen generation performance. (5th September 2019) - Hou, Xiaojiang; Wang, Yi; Hu, Rui; Shi, Hongchang; Feng, Lei; Suo, Guoquan; Ye, Xiaohui; Zhang, Li; Yang, Yanling
Summary: In this study, the metallurgical melting Mg‐10wt.%Ni (Mg10Ni) alloy is firstly modified by high‐energy ball milling (HEBM) and then surface catalysts expanded graphite (EG) or MoS2 or EG‐MoS2 are introduced to prepare Mg10Ni‐M (M = EG, MoS2, and EG‐MoS2 ) composites. The effects of surface catalysts on hydrolysis hydrogen generation of HEBM Mg10Ni alloy are comprehensively investigated. Their kinetics, rate‐limiting steps, and apparent activation energies are investigated by fitting the hydrolysis curves at different temperatures. The results indicate that the total hydrogen generation capacities of prepared Mg10Ni‐M (M = EG, MoS2, and EG‐MoS2 ) composites are 200, 170, 674, and 720 mL·g −1 within 1 minute at 291 K. The capacity and yield of Mg10Ni are 500 mL·g −1 and 56% within 15 minutes. The surface catalysts EG or MoS2 or EG‐MoS2 can distinctly elevate the initial H2 produce rate and promote the complete hydrolysis process. The highest capacity and generation yield within 15 minutes are 740.8 mL·g −1 and 91% obtained by HEBM Mg10Ni‐EG‐MoS2 composite at 291 K. The surface catalysis can promote high generation yield of Mg10Ni alloy in a short time. Abstract : As‐cast Mg‐10wt.%Ni (Mg10Ni) alloy is firstly modified by high energy ball milling (HEBM), and then expanded graphite (EG) or MoS2 or EG‐MoS2 is introduced to prepare Mg10Ni‐M (M = EG, MoS2, and EG‐MoS2 ) composites. The results indicate that the total hydrogen generation capacities of prepared Mg10Ni‐M composites are 200, 170, 674, and 720 mL·g‐1 within 1 minute at 291 K. The highest capacity and generation yield within 15 minutes are 740.8 mL·g‐1 and 91% obtained by Mg10Ni‐EG‐MoS2 at 291 K.